2001
DOI: 10.1136/jech.55.5.316
|View full text |Cite
|
Sign up to set email alerts
|

Long working hours and risk for hypertension in Japanese male white collar workers

Abstract: Study objective-To evaluate the association of long working hours with the risk for hypertension. Design-A five year prospective cohort study. Setting-Work site in Osaka, Japan. Participants-941 hypertension free Japanese male white collar workers aged 35-54 years were prospectively examined by serial annual health examinations. Men in whom borderline hypertension and hypertension were found during repeated surveys were defined as incidental cases of borderline hypertension and hypertension. Conclusions-These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 26 publications
7
89
2
1
Order By: Relevance
“…Data from more than Japanese 50,000 workers from 4 companies were evaluated. The results showing an inverse association between overtime work and prevalence of hypertension contradicted two former studies (Artazcoz et al, 2009;Yang et al, 2006), but confirmed others (Wada et al, 2006;Nakanishi et al, 2001). Despite the large database, the authors highlighted the cross-sectional design as the main study limitation that left the possibility open of residual effects of potential confounders and differences in assessments of overtime and blood pressure evaluation among the companies.…”
Section: Health and Working Timecontrasting
confidence: 54%
“…Data from more than Japanese 50,000 workers from 4 companies were evaluated. The results showing an inverse association between overtime work and prevalence of hypertension contradicted two former studies (Artazcoz et al, 2009;Yang et al, 2006), but confirmed others (Wada et al, 2006;Nakanishi et al, 2001). Despite the large database, the authors highlighted the cross-sectional design as the main study limitation that left the possibility open of residual effects of potential confounders and differences in assessments of overtime and blood pressure evaluation among the companies.…”
Section: Health and Working Timecontrasting
confidence: 54%
“…Two studies (39,40) concerning the same all-male study population found that long workhours were associated with a reduced risk of developing hypertension. Nakanishi et al (39) showed that, over a 3-year period, those who worked 10 hours or more a day had an increased risk of developing hypertension (RR=0.58).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies had a case-referent design (28,46). There were five independent longitudinal studies (35,36,(38)(39)(40)(41), and two repeatedmeasures studies (30,47). Table 1.…”
Section: Methodological Characteristics and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nakanishi et al 4,5) observed the onset of hypertension in office workers at a Japanese construction company and found an inverse relationship: with the number of working hours, the percentage of those having developed hypertension decreased. The authors 6) also examined the relationship between working hours and the onset of mental and circulatory disorders, and could not find detrimental effects of long working hours.…”
mentioning
confidence: 99%